REINSURANCE ARRANGEMENTS ASSOCIATED WITH GUARANTEE LEGAL RESPONSIBILITIES - Santri, Selvi Harvia (LPPM STIH Putri Maharaja, 2023)
The use of diversion responsibility or reinsurance arrangements as a way for insurance companies to protect themselves from losses by cooperating with a reinsurance company. One reason for utilizing reinsurance is to distribute risk. Reinsurance becomes more understandable when insurance claims occur, and it is not possible to have reinsurance without having insurance first. The legal framework for insurance and reinsurance is explained in the Criminal Code or Law Number 40 of 2014 concerning business insurance. However, there is no provision that clearly defines what is meant by reinsurance, which can cause problems if there are insufficient answers regarding the company's reinsurance payment for losses. Therefore, legal certainty is necessary. The research objective is to determine the form of responsibility of the guarantor in reinsurance, and the normative law method is used. The Ex-Gratia Payment clause outlines the responsibility of the reinsurance company to the insured, allowing the insured to claim compensation from the insurer for reinsurance claims.